Trichodina heterodentata (Ciliophora) infestation on Prochilodus lineatus larvae: a host-parasite relationship study - Valladao, Gustavo Moraes Ramos [UNESP]; Gallani, Silvia Umeda [UNESP]; De Padua, Santiago Benites [UNESP]; Martins, Mauricio Laterca; Pilarski, Fabiana [UNESP] (Cambridge Univ Press, 2014)
Prochilodus lineatus is a freshwater fish species found in South America. It is common in aquaculture, but few studies regarding diseases of this fish have been performed. This study presents data of the occurrence of Trichodina heterodentata Duncan, 1977, as well as the pathological alterations detected by light and scanning electron microscopy (SEM). Twenty 20-day-old larvae were harvested from an earth pond and examined. Larvae showed erratic swimming on the pond edges and some had a whitish tegument. Larval smears were either impregnated with silver nitrate or stained with Giemsa stain to observe the taxonomic features of the ciliates. Five larvae were fixed in formalin solution for histopathological analysis, and another five specimens were fixed in glutaraldehyde for SEM. All larvae were diagnosed with a severe infestation by trichodinid T. heterodentata. Histological sections showed discrete hyperplasia of the gill filaments with subepithelial oedema of the secondary lamellae. In the SEM, suction areas were observed on the skin, gill and eye; corrosion and ulceration of the fins were associated with the bacterial presence of cocci on the lesions. This is the first report of T. heterodentata in P. lineatus that is responsible for an acute disease that culminates in larval mortality.
Keywords: fish diseases; ectoparasite; Trichodinidae; pathogen; histopathology; scanning electron microscopy